DETERMINATION OF THE AMMONIUM CONTENT OF POTASSIC ROCKS AND MINERALS BY CAPACITANCE MANOMETRY: A PRELUDE TO THE CALIBRATION OF FTIR MICROSCOPES - Boyd S.R. (My University, 1997)
Previous results for stepped-heating experiments on micas have been used to develop a sealed-ampoule technique for the determination of the ammonium contents of small samples (1-10 mg) of muscovite, biotite and whole-rock garnet-micaschists, by capacitance manometry. Co-existing muscovites and biotites from a garnet-mica-schist, gave the following results: [NH+4]Mu = 468 +/- 10 ppm (n = 4) and [NH+4]Bi = 1466 +/- 50 ppm (n = 4). [NH+4]Mu/[NH+4]Bi = 0.32 +/- 0.01 is in the range found previously by others who studied ammonium partitioning between muscovite and biotite by other methods. The δ15N values of muscovite (+ 15.5 +/- 0.9%%) and biotite (+ 15.4 +/- 0.7%%) were indistinguishable, suggesting minimal selective partitioning of the nitrogen isotopes between the two minerals. The single whole-rock value of + 16.6%% was perhaps slightly elevated compared to the mean values of the mineral separates but quite close to some of the individual measurements.The size of sample required for the technique (1-10 mg) is far smaller than those required for previous studies, being much closer to the spatial resolution of microscopes for Fourier transform infrared (FTIR) spectroscopy. Ammonium absorbs strongly in the infrared (notably at 1430 cm-1) and FTIR microscopy is potentially the fastest technique available for the determination of ammonium concentrations. It is hoped that the techniques described herein could be used to prepare a range of inter-laboratory standards which would allow for the calibration of these absorption bands, for all of the major minerals, permitting numerous detailed studies to be undertaken.
Keywords: AMMONIUM; ANALYSIS; CONTINENTAL CRUST; GEOCHEMISTRY; INFRARED SPECTROSCOPY; MASS SPECTROMETRY; STABLE ISOTOPES; STANDARD MATERIALS